Efficient diffusion of renewable energies: A roller-coaster ride - Carsten Helm; Mathias Mier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
When the supply of intermittent renewable energies like wind and solar is high, the electricity price is low. Conversely, prices are high when their supply is low. This reduces the profit potential in renewable energies and, therefore, incentives to invest in renewable capacities. Nevertheless, we show that perfect competition and dynamic pricing lead to efficient choices of renewable and fossil capacities, provided that external costs of fossils are internalized by an appropriate tax. We also investigate some properties of electricity markets with intermittent renewables and examine the market diffusion of renewables as their capacity costs fall. We show that the intermittency of renewables causes an S-shaped diffusion pattern, implying that a rapid build-up of capacities is followed by a stage of substantially slowerdevelopment. While this pattern is well known from the innovation literature, the mechanism is new. We also find that technology improvements such as better battery storage capacities have substantial effects not only on the speed of market penetration, but also on its pattern. Finally, fluctuations of energy prices rise with the share of renewables. If regulators respond with a price cap, this leads to a faster market diffusion of renewables.
Keywords: Q21; D24; Q28; 330